2007
DOI: 10.1080/02688690701392881
|View full text |Cite
|
Sign up to set email alerts
|

Extended subcutaneous tunnelling technique for external ventricular drainage

Abstract: Infection is a serious complication of external ventricular drain (EVD) and various strategies have been adopted to minimize its occurrence. The use of an extended subcutaneous tunnel (50-60 cm) was previously described, but has since received little attention in the literature. The authors reviewed their experience with this technique, with emphasis on the rate of infection and predisposing risk factors. This is a retrospective review of 114 patients who received EVD with extended subcutaneous tunnel ('long E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 17 publications
2
21
0
1
Order By: Relevance
“…1,3,5,8,10,14,19,21) In coherence with the admitting diagnosis followed by operative intervention and an extended ICU abidance, these factors can be assumed to increase the risk of ventriculostomy-related infection. Our results showed that the ventriculostomy-related infection rate was significantly higher in secondary EVD placements compared to primary procedures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,3,5,8,10,14,19,21) In coherence with the admitting diagnosis followed by operative intervention and an extended ICU abidance, these factors can be assumed to increase the risk of ventriculostomy-related infection. Our results showed that the ventriculostomy-related infection rate was significantly higher in secondary EVD placements compared to primary procedures.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies showed that these antibiotic impregnated EVDs are superior compared to standard EVDs in this high risk patient subgroup. 8,10,14,19,21) Therefore, based on this knowledge, we decided to use only Bactiseal EVDs in these patients to guarantee the best patient outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported intracerebral hemorrhage rate due to ventriculostomy placement varies widely, ranging from 0 to 32.5% [1][2][3][4][5][6][7][8][9][10][11][12][13]. Recent peer-reviewed publications describe both the placement of ventriculostomies by non-neurosurgeons, and the implementation of alternative ventriculostomy techniques [5,7,8,13].…”
Section: Introductionmentioning
confidence: 98%
“…Aucoin et al reported a 6% increase in relative risk of infection for patients whose EVD was flushed www.intechopen.com with bacitracin solution (Aucoin, et al, 1986). A previously published report by the present authors also demonstrated intraventricular urokinase infusion as one of the risk factors for infection (Leung, et al, 2007). Historically, CSF was sampled routinely and indeed daily in some centers in an attempt to pick up early infections.…”
Section: Manipulation Of the Evd Systemmentioning
confidence: 99%